Exploring the impact of zinc oxide nanoparticles on fish and fish-food organisms: A review - Ahamadul Hoque Mandal; Surajit Ghosh; Ditipriya Adhurjya; Priyajit Chatterjee; Ishita Samajdar; Dip Mukherjee; Kishore Dhara; Nimai Chandra Saha; Giuseppe Piccione; Cristiana Roberta Multisanti; Shubhajit Saha; Caterina Faggio (Aquaculture Reports, 2024)
The uses and applications of nanoparticles in our daily lives and on an industrial scale are rapidly expanding as a result of scientific and technological advancements. The production and application of nanoparticles are the subjects of nanotechnology. The worldwide use of nanoparticles is increasing daily because of their potential use and applications in antibacterial, antifungal, anti-inflammatory, and wound healing properties. ZnO nanoparticles (ZnO-NPs) are very popular as a source in plastics, ceramics, glass, rubber paints, and food due to their high UV light absorption and reflective characteristics. Nonetheless, the high-water solubility of ZnO-NPs increases their toxicity in aquatic habitats. Concerns about ZnO-NPs are not restricted to the possible negative impact they could have on specific ecosystems, notably aquatic ones. These concerns also include the influence on the health of the species that live in these ecosystems, which has a knock-on effect that affects human health. For these reasons, this review article aims to carefully document the toxicity related to the occurrence of ZnO-NPs in water, which reflects on fish and fish-food organisms.